2007
DOI: 10.1016/j.cld.2007.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Lipid-Lowering Agents That Cause Drug-Induced Hepatotoxicity

Abstract: The effort to reduce cardiovascular risk factors, including hyperlipidemia, has led to the increased use of lipid-lowering agents. Hyperlipidemic patients often have underlying fatty liver disease, however, and thus may have elevated and fluctuating liver biochemistries. Therefore, caution should be applied before attributing elevated liver tests to lipid-lowering agents. Data indicate that patients who have chronic liver disease and compensated cirrhosis should not be precluded from receiving statins to treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
122
2
13

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(137 citation statements)
references
References 82 publications
0
122
2
13
Order By: Relevance
“…The most common adverse effect of niacin is skin flushing, which occurs in the majority of patients 115 . In addition, niacin can cause hepatotoxicity, hyperuricaemia, and hyperglycaemia 116,117 . The induction of hyperglycaemia and new onset diabetes mellitus by high doses of niacin can be harmful in patients with CKD, both with or without diabetes mellitus 118 .…”
Section: Niacinmentioning
confidence: 99%
“…The most common adverse effect of niacin is skin flushing, which occurs in the majority of patients 115 . In addition, niacin can cause hepatotoxicity, hyperuricaemia, and hyperglycaemia 116,117 . The induction of hyperglycaemia and new onset diabetes mellitus by high doses of niacin can be harmful in patients with CKD, both with or without diabetes mellitus 118 .…”
Section: Niacinmentioning
confidence: 99%
“…Our study also showed that there is no significant elevation of liver enzymes in statin group as feared due to the rare and dose related hepatotoxicity of statin. Some studies also showed that statins can cause diabetes mellitus and glucose intolerance, but in our study group all were DM-2 and they did not show elevated HbA1c levels as compared to non statin group [27][28][29][30] .…”
Section: Jmscr Vol||05||issue||03||page 18698-18708||march 2017mentioning
confidence: 70%
“…Ironically, several of these alternative agents are associated with clinically apparent hepatotoxicity as well (10). Maybe, it is just time for us to remember that more than nearly 1,000 drugs have been linked to abnormalities of liver function tests, the vast majority of which are only mild in nature.…”
Section: Invited Commentarymentioning
confidence: 99%